STRATEGI PEMETAAN KAWASAN DALAM MENENTUKAN LOKASI YANG TEPAT UNTUK AGROWISATA BUAH DI KABUPATEN SUMENEP - Rusnani ,; Ribut Santosa; Cholilul Chayati (Fakultas Ekonomi dan Bisnis, 2017)
The natural beauty of Sumenep city is a potential that can be developed into natural and agricultural tourism. Besides the beauty of nature there is also the potential of superior fruits of various kinds and abundant but not yet maximally empowered. The purpose of this research is to know the map of potential areas and the right location for fruit agro-tourism in Sumenep regency. The method used is quantitative method which is the process of exploring the existing potential and understanding the behavior of individuals and groups through samples used with purposive sampling technique, location analysis using Location Quotietient (LQ) motion with primary and secondary data Expected expected output location Right for Fruit Agrowisata Conclusion, the potential location for agro tourism is Batuuan Village Batuan Subdistrict, commodity of plants that have the potential to be developed are dragon fruit, serikaya, watermelon, melon, orange, guava, guava and jackfruit.An appropriate development model is agro tourism Community-based.Keywords : Potential Mapping, Fruit Agro tourism.